PENGARUH KONSERVASI LAHAN DAN PENERAPAN BIBIT UNGGUL TERHADAP PENDAPATAN PETANI DI KABUPATEN BOJONEGORO - EDY SUHARTONO (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2015)
Farmers Income Improvement Program through innovations have been implemented in Bojonegoro. The program helps farmers in developing agribusiness system on marginal lands that are considered as pockets of poverty. The purpose of this study was to determine the effect of simultaneous application of variable quality seeds and soil conservation on the income of farmers in Bojonegoro and determine variables that have a dominant influence on the income of farmers in Bojonegoro. The research data was collected through interviews guided questionnaire to a sample of 50 farmers involved Activities Farmers' Income Improvement Program through Innovation. The collected data is then processed using the F test and t test. Results showed simultaneously using the F test indicated the presence of markedly between the Program for Increasing Farmers' Income through innovation (application of seeds (X1) and land conservation (X2)) and the income of farmers of marginal land in the District Sugihwaras Bojonegoro, indicated by F count (26.726)> F table at 2.806. Being the variable component of the most influential innovations is the application of seeds (X1) affect the value of t = 4.683> t table = 1.678.